Application of green-emitting Sr3WO6:U phosphor to enhance lumen efficiency of WLEDs - Phuc Dang Huu; Ton That Phung (Bulletin of Electrical Engineering and Informatics, 2022)
The article demonstrates a sample of spectrum in the phosphor-covered WLED (abbreviated as p-WLED) containing one blue chip, one red chip along with phosphors of green and yellow colors. We acquired the p-WLEDs’ ideal spectrum in the CCTs, which is short for correlated color temperature range from 2700 K to 6500 K using a nonlinear program in order to optimize the radiation’s lumen efficiency (LER) when the R9 strong red's color rendering indexes (CRIs) and special CRIs exceed 98. From the outcomes of the recreation, p-WLEDs containing an InGaN blue chip with 450 nm wavelength, an AlGaInP red chip with 634 nm wavelength, along with green and yellow silicate phosphors with the value of 507 and 580 nm wavelength correspondingly; can produce white lights with CRI values of around 98 and particular CRI values of R9 for intense reds above 98. For saturated red, yellow, green, and blue colors, the average values of the particular CRIs R9 through R12 exceed 95. In CCT values of 2700 K to 6500 K, the R13 value in female figures is around 100, with LER values reaching 296 lm/W.